Pengalaman Belanja Berbasis AI: Augmented Reality sebagai Strategi PR Digital Berkelanjutan dalam Industri Kecantikan - Lutfiana, Diana Lutfiana; Erlita, Novi; Romaria, Gustina (LPPM Universitas Bina Sarana Informatika, 2024)
Augmented Reality (AR) has become an essential part of digital marketing strategies in the beauty industry. This technology enables deeper virtual interactions for consumers, enhances the shopping experience, and strengthens digital Public Relations (PR) strategies. This study analyzes the impact of AR usage in beauty e-commerce on consumers' purchase intentions and the sustainability of digital brand communication. Using a quantitative approach, the study collected data from 250 respondents who use Shopee BeautyCam. The results indicate that AR in e-commerce enhances consumer trust, provides a more personalized shopping experience, and supports sustainability goals in SDG 9 (Industry, Innovation, and Infrastructure). The AR feature also contributes to reducing waste from physical product testers and improving digital marketing efficiency by optimizing online consumer interactions. Moreover, AR offers brands an opportunity to connect more deeply with consumers through immersive and engaging experiences, boosting customer loyalty. As a result, AR not only drives sales but also fosters stronger long-term relationships between brands and consumers. This sustainability further enhances the brand's image, aligning it with environmental and social sustainability issues, which are increasingly important to today’s consumers.